Increasing Students’ Reading Comprehension Using Humor Story - Mangowal, Calvin; Liando, Nihta v. F.; Rorimpandey, Rinny (Program Studi Pendidikan Bahasa Inggris, 2025)
The purpose of the study is to find out whether the use of humor stories in teaching reading can improve student’s reading comprehension to the second grade students. This is a quantitative research, and a reading test in multiple-choice format is use to collect data. Two narrative texts with ten multiple choice items each to consist the test. The test is using for both pretest and posttest. It was involve 35 students’ second grade of SMP Negeri 2 Amurang in the 2021/2022 academic year. The data analysis leads to the following result: calculation of mean of pretest and posttest data was done using the formula previously mentioned. Thus, with ∑X = 168, ∑Y = 206 and n = 35, mean of pretest was 4.8, whereas mean of the posttest was 5.9. The calculation indicates that posttest mean (5.9) is bigger than that of the pretest, 4.8. In other words, it means that students reading performance in the posttest is better than their performance before the treatment. This is due to the application of Humor Story. Standard deviation, as pointed out earlier, was calculated using raw scoring formula. Thus, with ∑X2 = 860, pretest mean 23.0, and n = 35, the standard deviation of pretest was 1.6; with ∑Y2 = 1264, mean = 34.8, and n = 35, the standard deviation of posttest was 1.3. The result of standard deviation calculation indicates that students reading performance in the pretest or before the treatment is more heterogeneous than their performance after the treatment